Sistem Informasi Geografis Pemetaan dan Analisis Lahan Pertanian di Kabupaten Deli Serdang - Ali Ikhwan; Rifki Ade Ananda; Nazli Adittra; Muhammad Abdi Pulungan; Refnaldi Prayoga (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to develop a Geographic Information System (GIS) for mapping and analyzing agricultural land in Deli Serdang Regency, North Sumatra. The system was designed using the Rapid Application Development (RAD) method to speed up the development process and ensure the system meets user needs. The research results show that GIS is able to provide effective solutions to agricultural data management problems, such as mapping harvest area, potential empty land, and distribution of production results. in real time. With an easy-to-use interface, this system supports efficient crop distribution, data-based policy development, and sustainability of the agricultural sector. This research suggests developing additional features such as predictive analysis, user training, and regular evaluation to optimize the benefits of GIS in supporting sustainable agricultural development.